Sistem Monitoring Sungai Berbasis IoT - Pambudi, Arga Dwi; Wulandari, Sari Ayu (Universitas Semarang, 2022)
Water pollution often occurs due to the disposal of household waste (solid waste and liquid waste) as well as industrial waste, small industry and non-organic waste. This waste will be disposed of through channels which then flow into rivers. Thepurpose of this research is to make a device that can determine the condition of river water, which is polluted or not from along distance. The method used in this study is by taking samples from river water that can represent polluted and unpolluted,then data is taken from these samples which are then processed so that their condition can be known. The conditions that havebeen obtained are then displayed via the web.